Strategies for Minimizing Material Waste with the Application of Lean Construction in Building Construction Projects - Juniawan, Ngakan Agung Biben; Putera, I Gusti Agung Adnyana; Aribudiman, I Nyoman (Journal of Asian Multicultural Research for Economy and Management Study, 2024)
Waste of construction materials is one of the problems often experienced by several construction service actors in Bali, especially in Gianyar, the utilization of materials is not efficient so that the project experiences cost overruns. The purpose of this study is to identify the dominant indicators causing building construction material waste and formulate strategies to minimize material waste by applying lean construction principles to building construction projects. The research sample was 15 small-scale contracting companies in Gianyar with 2 to 3 respondents in each company, namely directors, site managers and implementers. Data collection using questionnaires. The data processing technique used is factor analysis and focus group discussion. The test results show that there are 10 indicators of the causes of material waste that often occur, namely, the design does not adjust the size of the available materials, lack of knowledge about construction implementation techniques, drawings with volume calculations are not well integrated, construction materials cannot be stored for a long time, excessive mixture of wet materials, distant material storage locations, incorrect use of conventional formwork, lack of periodic checks related to work results, installed material specifications are not appropriate, lack of attention to material specifications on site. The results of the focus group discussion found that the strategies to reduce material waste based on the application of lean construction principles are training for workers involved, scheduling good material procurement, using standard components available on the market by taking into account modules that can be applied, increasing communication with various parties in exchanging information through discussion forums, checking work results and material specifications regularly.